Case Study : Ayam Warisan Venture / Fatin Adilla Che Abdul Rahman - Che Abdul Rahman, Fatin Adilla (2020)
This assignment is focus on a case study of the company, Ayam Warisan that located at Guar Chempedak in Kedah. For this purpose, I have interview session with the owner about the company information an do SWOT analysis. Learning the current condition of strength weaknesses, opportunities and threats can help a development in the business strategies. This strategy to enhance the technology and marketing of the business is very critical thing because we must brave in order to try a new methodology. Besides, the problems finding from the company is by the SWOT analysis and how the owner come out with the solution to handle the problems.